Mobile Learning Apps in Instruction And Students Achievement - Kattayat, Sandhya; Josey, Smitha; J.V, Asha (International Journal of Interactive Mobile Technologies (iJIM), 2017)
The increasing availability of low-cost mobile and wireless devices and associated infrastructure heralds both opportunities and challenges for educational institutions and their teachers and learners.[1]Mobile telephones are inexpensive, accessible, and well positioned for the delivery of student support interventions. Low cost mobile technologies can be used to maintain and enhance contact with students and teachers, and, by logic and improve retention[2]Students reasons for withdrawal from a course can be due to: distance from the study centres; insufficient academic support; insufficient information on counselling and laboratory sessions; and other associated information. As mobile phones become more ubiquitous, they are arguably well positioned to play a more central and effective role in providing students with much needed information – i.e., schedule of counselling and/ or laboratory sessions; and other relevant information related to their studies.[3]Most learning pedagogies from constructive learning and conversation theories can be adapted for a mobile learning environment. The key is to understand the strengths and weakness of a particular technology, while deploying good pedagogical practices to achieve specific learning goals.[3]It seems inevitable that m-learning will soon be an essential extension of e-learning[3] In the context of mobile learning, device type has a critical impact on teaching and learning.[4] Mobile learning is most prevalent at higher education institutions, followed by elementary schools. Mobile learning most frequently supports students in the professions and applied sciences, followed by the humanities and formal sciences. The most highly cited articles fall into the categories of mobile learning system design and followed by effectiveness. In sum, this study of issues in mobile learning presents findings which can help supplement linkages with previous studies and forms an important reference base for the future research in mobile learning.[4]The basic elements of mobile learning are teacher , learner, content, environment and assessment.[7]